Dinâmica do tiametoxam em plintossolo sob aplicação de biochar e seu efeito sobre as propriedades microbianas do solo - Peres, Fernanda Salles Cunha (2019)
Thiamethoxam is an agriculturally effective insecticide, its high mobility and persistence cannot result in groundwater contamination and adhesion in biogeochemical cycles. In this sense, the use of organic materials with high stability and reactivity, such as biochar, may be an alternative to mitigate the potential for deleterious impact of this molecule on the environment. The aim of this study was to verify the duration of biochar application in a study on sorption and desorption of tiametoxam insecticide, and the soil microbial properties in response to fertilization with NPK and an application of tiametoxam insecticide. The samples were collected in an experiment conducted in a randomized block design by combining doses of NPK mineral fertilizer (0 and 300 kg ha-1 of form 05-25-15) and biochar (0, 8, 16 and 32 t ha-1 ). Soil samples were collected from all phases in the 0 to 0.10 m layer which determined: i) sorption and desorption of tiametoxam insecticide in soil, quantification of soil organic matter (SOM), carbon content in humic fractions SOM through chemical fractionation and soil organic carbon; ii) soil enzymatic activity, microbial biomass carbon (CBM), basal microbial respiration rate (C-CO2) and quotient (qCO2). After the first soil sampling, an insecticide was applied to an experimental sample, and a soil sample was taken to determine the microbiological attributes. A Freundlich isotherm suited one species of thiametoxam in all treatments. The application of biochar provided increased sorption and reduced desorption of thiametoxam. Sorption intensity showed decreasing characteristics as they accumulate as soil tiametoxan concentrations, characteristics of hysteresis expression. The biochar has an orderly effect on the soil by covalently bonding with insecticide molecules and indirectly increasing the sorption potential in the chemical fractions of soil organic matter. The application of 32 t ha-1 of biochar reduced to zero as thiamethoxam concentrations in the soil solution below 60 cm in the soil profile. Thus, a biochar applicability to the soil is a potential tool in mitigating the contaminant potential of agrochemicals in subsurface waters. In soil microbials, biochar promoted enzymatic elevation of urease, acid phosphatase, basal respiration and qCO2, and reduction of CBM. The application of biochar at higher doses is 16 t ha-1 resulting in increased CO2 production and reduced Plinthosol CBM. The insecticide thiametoxam suppressed the enzymatic activity of acid phosphatase, urease, resulting in increased alkaline phosphatase and reduced soil basal respiration. The application of biochar in the soil did not attenuate the effects of thiametoxam on the soil microbiota.